A Novel Glycerol Kinase Gene OsNHO1 Regulates Resistance to Bacterial Blight and Blast Diseases in Rice - Xiao, Xiaorong; Wang, Rui; Khaskhali, Shahneela; Gao, Zhiliang; Guo, Wenya; Wang, Honggang; Niu, Xiaolei; He, Chaoze; Yu, Xiaohui; Chen, Yinhua (Frontiers in Plant Science, 2022)
Glycerol-induced resistance to various pathogens has been reported in different plants. Glycerol kinase (GK), a vital rate-limiting enzyme that catalyzes glycerol conversion to glycerol-3-phosphate (G3P), participates in responses to both abiotic and biotic stresses. However, its physiological importance in rice defenses against pathogens remains unclear. In this research, quantification analysis revealed that GK levels were significantly induced in rice leaves infected by Xanthomonas oryzae pv. oryzae (Xoo) strain PXO99. A typical GK-encoding gene OsNHO1 was cloned in rice. The transcriptional levels of OsNHO1 were significantly induced by salicylic acid, jasmonic acid, and Xoo-PXO99. Ectopic expression of OsNHO1 partially rescued the resistance to P. s. pv. phaseolicola in the Arabidopsis nho1 mutant. In the over-expressing transgenic rice lines (OsNHO1-OE), the content of GK and the transcriptional level of OsNHO1 were increased and the resistance to bacterial blight and blast was improved, while reduced OsNHO1 expression impaired the resistance in OsNHO1-RNAi lines. The wax contents and expression of the wax synthesis regulatory genes were significantly increased in the overexpression lines but decreased in the OsNHO1-RNAi lines. We then confirmed the interaction partner of OsNHO1 using yeast two-hybrid and bimolecular fluorescence complementation assays. The transcription of the interaction partner-encoding gene OsSRC2 and OsPRs in OsNHO1-RNAi lines were down-regulated but up-regulated in OsNHO1-OE lines. Thus, we concluded that OsNHO1 provided disease resistance by affecting the wax content and modulating the transcription levels of PR genes.